Traumatic Brain Injury in Juvenile Offenders: Findings From the Comprehensive Health Assessment Tool Study and the Development of a Specialist Linkworker Service. Issue 2 (March 2015) - Chitsabesan, Prathiba; Lennox, Charlotte; Williams, Huw; Tariq, Omar; Shaw, Jenny
Abstract : Background: Young people in contact with the youth juvenile justice system have well-documented vulnerabilities including high rates of mental health and neurodevelopmental disorders. Studies have suggested that they may also be at increased risk of traumatic brain injury (TBI). Objective: (1) To describe the profile of a cohort of juvenile offenders with TBI and associated comorbidity with other neurodevelopmental disorders, mental health needs, and offending behavior. (2) To describe the development of a specialist brain injury service for juvenile offenders with TBI within custody. Methods: Ninety-three male participants aged 15 to 18 years were consecutively admitted to a custodial secure facility. They were evaluated using a range of different neurocognitive and mental health measures including the Rivermead Post-Concussion Symptoms Questionnaire and the Comprehensive Health Assessment Tool. Results: Eight-two percent of those interviewed reported experiencing at least 1 TBI, and 44% reported ongoing neuropsychological symptoms. Eighteen percent of those sustaining a TBI reported moderate-severe postconcussion symptoms. Conclusions: There is a high prevalence of TBI in juvenile offenders in custody, with many experiencing multiple episodes. This study highlights the need for further research in this area. An example of a specialist brain injury linkworker service is described as one example of a model of service delivery for this group.